2015
DOI: 10.1002/chem.201501626
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Emissive and Photostable Four‐Coordinate Organoboron N,C Chelates and Their Use in Fluorescence Microscopy

Abstract: Six strongly fluorescent four-coordinate organoboron N,Cchelates, containing an arylisoquinoline skeleton, were prepared. Remarkably, the fluorescence quantum yields reach values of up to 0.74 in oxygen-free toluene. The strong B-N interaction was corroborated by the single-crystal X-ray analysis of two dyes. The intramolecular charge-transfer (ICT) character of the fluorophores was evidenced by solvatochromic studies and time-dependent density-functional-theory calculations at the PCM(toluene)/CAM-B3LYP/6-311… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(125 citation statements)
references
References 65 publications
(158 reference statements)
10
112
0
Order By: Relevance
“…The key data are summarized in Table and spectra are shown in Figure . The dyes 10 and 11 show a typical long‐wavelength absorption band at λ >400 nm, that has been already seen for the analogous dye that lacks the additional phenyl substitution at the 8‐position of the naphthalene . However, in the case of dye 12 this band is just observed as a shoulder and with a smaller molar absorption coefficient.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The key data are summarized in Table and spectra are shown in Figure . The dyes 10 and 11 show a typical long‐wavelength absorption band at λ >400 nm, that has been already seen for the analogous dye that lacks the additional phenyl substitution at the 8‐position of the naphthalene . However, in the case of dye 12 this band is just observed as a shoulder and with a smaller molar absorption coefficient.…”
Section: Resultsmentioning
confidence: 59%
“…The stronger electron‐donating ‐NMe 2 shifts the emission maximum even close to 600 nm. These new BAI dyes usefully complement a previously investigated series of racemic BAI dyes with demonstrated applications in bioimaging . Further, this work provides an attractive path for the design of spectrally fine‐tuned emission of CPL‐SOM architectures …”
Section: Introductionmentioning
confidence: 78%
“…To assess the potential of our new BOBIPY series for biological applications, we next studied its stability under different conditions, using 4 f as reference. Similar structures have been shown to be stable to nucleophilic substitution processes, photochemical reactions, temperature variations and in buffered solutions . We thus focused on the stability of the fluoroborane group as this had not been previously established.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our research program we have been interested in arylisoquinolines as chelate ligands for organoboron dyes (BAI dyes) with specific focus on their appropriateness for bioimaging with confocal or multiphoton fluorescence microscopy . In a recent work we have demonstrated that four‐coordinate N,C‐chelate dyes such as the ones shown in Figure (dye 1 – 4 ) are interesting candidates for these applications .…”
Section: Introductionmentioning
confidence: 99%